Characteristics of Antibiotic Resistance Genes and Antibiotic-Resistant Bacteria in Full-Scale Drinking Water Treatment System Using Metagenomics and Culturing - Gu, Qihui; Sun, Ming; Lin, Tao; Zhang, Youxiong; Wei, Xianhu; Wu, Shi; Zhang, Shuhong; Pang, Rui; Wang, Juan; Ding, Yu; Liu, Zhenjie; Chen, Ling; et al. (Frontiers in Microbiology, 2022)
The contamination of antibiotic resistance genes (ARGs) in drinking water sources may pose a direct threat to human health. In this study, metagenomic approach was used to investigate the ARG profile in a drinking water treatment system (DWTS) of south China. In general, a total of 317 ARG subtypes were detected, especially genes encoding bacitracin, multidrug, and sulfonamide were widely detected in DWTS. Putative ARGs host Acidovorax(6.0%), Polynucleobacter(4.3%), Pseudomonas(3.4%), Escherichia(1.7%), and Klebsiella(1.5%) were the enriched biomarkers in DWTS, which mainly carried bacitracin, beta-lactam and aminoglycoside ARGs. According to further analysis of ARG-carrying contigs (ACCs), Stenotrophomonas maltophilia and Pseudomonas aeruginosa were most common pathogens among 49 ACCs pathogens in DWTS. Metagenomic binning results showed that 33 high-quality Metagenome-Assembled Genomes (MAGs) were discovered in DWTS, particularly the MAG which was identified as Stenotrophomonas maltophilia-like (bin.195) harboured the greatest number of ARG subtypes (n=8), including multidug (n=6;smeD, semE,multidrug_transporter,mexE,semB,and smeC),beta-lactam (n=1;metallo-beta-lactamase), and aminoglycoside (n=1;aph(3’)-IIb), respectively. The strong positive correlation between MEGs and ARGs subtypes revealed a high ARG dissemination risk in DWTS. Based on the pure-culture method, ninety-three isolates that belong to 30 genera were recovered from DWTS. Especially, Multi-Drug Resistant (MDR) pathogens and opportunistic pathogens such as Pseudomonas aeruginosa, Bacillus cereus, and Stenotrophomonas maltophilia were detected in DWTS. These insights into the antibiotic resistome of DWTS indicated the need for more comprehensive ARGs monitoring and management in DWTS. Furthermore, more effective disinfection methods need to be developed for the removal of ARGs in DWTS. Our findings could assist governing bodies in surveillance of antibiotic resistance in DWTS.